Inappropriate long-term use of antipsychotic drugs is common among people with dementia living in specialized care units - Gustafsson, Maria (BioMed Central, 2013)
BACKGROUND: Antipsychotic drugs are widely used for the treatment of Behavioral and Psychological Symptoms of Dementia (BPSD), despite their limited efficacy and concerns about safety. The aim of this study was to describe antipsychotic drug therapy among people with dementia living in specialized care units in northern Sweden. METHODS: This study was conducted in 40 specialized care units in northern Sweden, with a total study population of 344 people with dementia. The study population was described in regard to antipsychotic drug use, ADL function, cognitive function and BPSD, using the Multi-Dimensional Dementia Assessment Scale (MDDAS). These data were collected at baseline and six months later. Detailed data about antipsychotic prescribing were collected from prescription records. RESULTS: This study showed that 132 persons (38%) in the study population used antipsychotic drugs at the start of the study. Of these, 52/132 (39%) had prescriptions that followed national guidelines with regard to dose and substance. After six months, there were 111 of 132 persons left because of deaths and dropouts. Of these 111 people, 80 (72%) were still being treated with antipsychotics, 63/111 (57%) with the same dose. People who exhibited aggressive behavior (OR: 1.980, CI: 1.515-2.588), or passiveness (OR: 1.548, CI: 1.150-2.083), or had mild cognitive impairment (OR: 2.284 CI: 1.046-4.988), were at increased risk of being prescribed antipsychotics. CONCLUSION: The prevalence of antipsychotic drug use among people with dementia living in specialized care units was high and inappropriate long-term use of antipsychotic drugs was common.